ESBL-Producing Salmonella enterica Serovar Typhi in Traveler Returning from Guatemala to Spain - Anna Fàbrega (Emerging Infectious Diseases, 2014)
We report a case of typhoid fever in a traveler returning to Spain from Guatemala that was caused by Salmonella enterica serovar Typhi which produced an extended-spectrum β-lactamase (ESBL). This finding demonstrates the presence of ESBL-producing S. enterica ser. Typhi strains in the Americas. Enhanced surveillance is necessary to prevent further spread.